2021
DOI: 10.5553/benm/138900692021048002005
|View full text |Cite
|
Sign up to set email alerts
|

‘We gaan het gewoon doen!’

Abstract: Inleiding'U heeft dus, samen met uw collega's op school, de schoolleiding en uw schoolbestuur, zélf de ruimte om keuzes te maken. Keuzes die passen in uw visie op onderwijs en op wat het beste is voor uw leerlingen. Er is dus meer ruimte in regels dan u misschien wel denkt.' (Onderwijsinspectie, 2017, 7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This study showed how this could also feed back into the organizational environment by relieving staff members of supervisory tasks. Rethinking dementia care by radically altering the physical, social and organizational environment to better meet the needs of residents indicates a rebellion-like mindset of the founders ( 27 , 55 ). This includes creating an environment, which is focused on seeing the person beyond the disability, instead of the convenience of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed how this could also feed back into the organizational environment by relieving staff members of supervisory tasks. Rethinking dementia care by radically altering the physical, social and organizational environment to better meet the needs of residents indicates a rebellion-like mindset of the founders ( 27 , 55 ). This includes creating an environment, which is focused on seeing the person beyond the disability, instead of the convenience of the organization.…”
Section: Discussionmentioning
confidence: 99%